Correlation Between Radiographic Grading of Osteoarthritis, Pain Severity and Functional Status in Knee Osteoarthritis Patients - Khairina, Annisa Dwi; Moeliono, Marina A.; Rahmadi, Andri Reza (Althea Medical Journal, 2018)
Background: Osteoarthritis is a joint degenerative disease characterized with structural changes of joint. The structural changes can be assessed with radiological assessment. Major clinical manifestations may include pain, inflammation, and stiffness, resulting in limitations for performing daily activities. The purpose of this study was to determine the correlation between radiographic grading of osteoarthritis, pain severity, and lower extremities functional status in patients with knee osteoarthritis.Methods: The study involved 29 patients with knee osteoarthritis in Dr. Hasan Sadikin General Hospital, Bandung and Bandung District General Hospital during the period of August to October 2014 using the cross sectional method. This study used NRS (Numeric Rating Scale) for pain severity assessment, Kellgren-Lawrence criteria for radiographic grading of osteoarthritis, and Modified Lower Extremity Funcional Scale for functional status assessment. The data were analyzed using statistical analysis tools. If the data were normally distributed, the correlation test will be carried outÂ by using the Pearson correlation test and if the data were not normally distributed then the Spearmanâs Correlation test will be used.Results: Correlation coefficient between severity of pain and functional status is r= -0,439 with p value= 0.17 (p<0.05). There was no significant correlation between radiographic grading of osteoarthritis and functional status (p > 0.05).Conclusions: The severity of pain correlates with the functional status of patients with osteoarthritis of the knee, while radiographic grading of osteoarthritis does not correlate with functional status.Â Keywords:Â